Predicting zinc-enhanced maize hybrid performance under stress conditions - Goredema-Matongera, Nakai; Thokozile Ndhlela; Biljon, Angeline van; Labuschagne, Maryke T. (Wiley, 2023)
The low yield potential of most biofortified maize is a barrier to its full adoption and reduces its potential to curb various macro- and micronutrient deficiencies highly prevalent in low-income regions of the world, such as sub-Saharan Africa (SSA). By crossing biofortified inbred lines with different nutritional attributes such as zinc (Zn), provitamin A and protein quality, breeders are attempting to develop agronomically superior and stable multi-nutrient maize of different genetic backgrounds. A key question, however, is the relationship between the biofortified inbred lines per se and hybrid performance under stress and non-stress conditions. In this study, inbred line per se and testcross performance were evaluated for grain yield and secondary traits of Zn-enhanced normal, provitamin A and quality protein maize (QPM) hybrids and estimated heterosis under combined heat and drought (HMDS) and well-watered (WW) conditions. Responses of all secondary traits, except for the number of days to mid-anthesis, significantly differed for HMDS and WW conditions. The contribution of heterosis to grain yield was highly significant under both management levels, although higher mid and high-parent heterosis was observed under WW than HMDS conditions. However, the findings suggest that inbred line performance was the best determinant of hybrid performance under HMDS. Strong correlations were observed between grain yield and secondary traits for both parents and hybrids, and between secondary traits of inbred lines and hybrids under both management levels, indicating that hybrid performance can be predicted based on intrinsic inbred line performance. Phenotypic correlation between grain yield of inbred lines and hybrids was higher under HMDS than WW conditions. This study demonstrated that under HMDS conditions, performance of Zn-enhanced hybrids could be predicted based on the performance of their corresponding inbred lines. However, the parental inbred lines should be systematically selected for desirable secondary traits correlated with HMDS tolerance during inbred line development.